Analysis Of The Chemistry Book For The Third Grade Medium On The Skills Of The 21st Century - et. al., Asst. Prof. Dr. susan duraid Ahmed (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
: The current study aims to analyze the content of the chemistry book for the third middle grade according to the skills of the 21st century for the academic year (2020-2021). To achieve this goal, a list of 21st century skills to be included in the chemistry book for the third grade was built after a series of literature, research and previous studies, as the 21st century skills tool was built with its main and sub-skills in its initial form consisted of (68) indicators distributed in three main groups and presented the list to a group of specialists in the field of curriculum and teaching methods, Thus the tool was formed in its final form of (59) sub-issue, and then analyzed the content of the chemistry book for the third grade intermediate in light of the tool skills of the 21st century and the analysis included three books in the reality (111) pages and adopted the explicit and implicit idea of a unit for recording and repetition, and the researcher found the sincerity of the analysis by presenting a random sample of analysis to a group of arbitrators and they agreed on the validity of the analysis Using the Holiste equation, stability was calculated in agreement with external analysts and with the researcher herself, and one of the most important findings of the researcher was that the chemistry book for the third grade average dissonance obtained a percentage (43.76%) By (658) repetitions In the light of the results of the research, the researcher came up with a number of recommendations, including:-: 1 -Attention to the principle of integration between the topics of books and include them what is modern. 2 -Training teachers in educational and educational practices that lead to the development of all skills and development among learners by employing educational experiences and attitudes to apply research and exploration behavior using the skills of the 21st century. 3 -The need to conduct educational courses and workshops for teachers to increase their awareness of the importance of 21st-century skills. . The researcher suggested completing this study several proposals, including:- 1-Study sing the level of awareness of 21st-century skills among teachers, supervisors, and school principals. 2-Study on the obstacles of developing the skills of the 21st century and developing proposed solutions.